“Ensayo de tres (03) fuentes y tres (03) dosis de abonos orgánicos en el rendimiento de soya variedad cristalina (glycine max (L) merril caspizada región San Martín” - Pinedo Ramírez, Elvis (2002)
In the present research work, the application effect of three sources and three dose of organic payments were evaluated (Worm Humus, Bovine Manure and Hens Manure), in soya crops, comparing with a witness without any payments and to demonstrate what sources and what levels that you even choose they are those but favorable to increase the yields. The study was made in Caspizapa district, province of Picota, Region of San Martin to 73 Kilometers from Tarapoto city. The objetives of this work were to determine the sources and the security dose but adapted in the soya cultivation, Crystalline variety that produces high yields under tropical dry forest condi~ions and ·to determine the production costs of different treatments and their cost benefit. Relationship. lt . Was used the design at random in Complete Blocks with factorial arrangement 3 x 4 and three · repetitions for each treatment. The distancing sow was of 0.50 m between arrays and 0.20 m among plants .. The yields for the sources are: hen manure 3636 Kg/He, Worm Humus 3605 · Kg/He, Bovine Man u re 3358 Kg/He; likewise with regard to the dose the following is reported: 40 TM/He 3920 Kg/He, 15 TM/He 3519 Kg/He, 3 TM/He 3161 Kg/He, o TM/ha 2666.33 Kg/He; and is obtained for the interaction the following: T1 = 4019 Kg/Ha (Worn Humus 40 Tm/Ha) T2 = 3611 Kg/Ha (Worn Humus 15 Tm/Ha) T3 = 3185 Kg/Ha (Worn Humus 3 Tm/Ha) T4 = 2685 Kg/Ha (Witness) T 5 = 3667 Kg/Ha (Bovine Manure 40 Tm/Ha) T s = 3352 Kg/Ha (Bovine Manure 15 Tm/Ha) T 1 = 3056 Kg/Ha (Bovine Manure 3 Tm/Ha) Ts = 2740 Kg/Ha (Witness) T s = 407 4 Kg/Ha (Birds Manure 40 Tm/Ha) T10 = 3593 Kg/Ha (Birds Manure 15 Tm/Ha) T 11 = 3241 Kg/Ha (Birds Man u re 3 Tm/Ha) T12 = 2574 Kg/Ha (Witness). There are statical differences among the trataments, of those which the security source with manure of birds with 3241 Kg/Ha to the dose of 3 TM/Hathe one that reach the biggest profitability with 22.82% was.